Thrombolytic treatment in acute myocardial infarction: neutrophil activation, peripheral leucocyte responses, and myocardial injury. - Ranjadayalan, K (1991)
OBJECTIVE--To examine early leucocyte responses and neutrophil activation in acute myocardial infarction treated by streptokinase and to relate the findings to coronary recanalisation and indices of myocardial damage in order to provide further information about the role of neutrophils in the evolution of injury. DESIGN--Group analysis of paired blood samples, obtained before streptokinase treatment and one hour after it, and of three indirect measures of myocardial injury: left ventricular ejection fraction, QRS score, and peak creatine kinase. SETTING--The coronary care unit of a district general hospital. PATIENTS--39 patients with acute myocardial infarction who underwent paired blood sampling (before streptokinase and one hour after streptokinase) and cardiac catheterisation 5 (3-8) days later. END POINTS--Changes in peripheral white cell and neutrophil counts and plasma elastase one hour after streptokinase infusion. Comparison of these variables in patients with and without patency of the infarct related coronary artery. Correlations between these variables and indirect measures of myocardial injury. RESULTS--Neutrophil activation, as reflected by plasma elastase, increased sharply one hour after streptokinase. Total white cell and neutrophil counts also increased. Changes tended to be more pronounced in patients with patency of the infarct related artery, though the trend was not statistically significant. Neutrophil activation before streptokinase was unrelated to indirect indices of myocardial injury but only one hour after streptokinase a weak negative correlation with left ventricular ejection fraction had developed. Peripheral neutrophil responses showed a similar relation to ejection fraction and also correlated with peak creatine kinase and QRS score. CONCLUSIONS--Thrombolytic treatment in acute myocardial infarction is associated with an abrupt reactive neutrophil response which provides an early measure of injury. It is also associated with neutrophil activation, probably in response to coronary recanalisation and myocardial reperfusion. Activated neutrophils are recognised as mediators of reperfusion injury in experimental infarction and the data in the present study provide preliminary evidence of a similar pathogenic role in the clinical setting.